Relationships Between :Metacognitive Awareness, Learning Styles, and Reading Comprehension in English Language Learning - Mokhtar, Ahmad Azman (2001)
The aim of this study was to determine the relationships between metacognitive awareness, learning styles, and reading comprehension. The study was conducted in the District of Hulu Langat with a total of 284 students who were randomly sampled from two boarding and two day schools. The Metacognitive Awareness Inventory (MAl) was used to assess the metacognitive awareness level of the students. The Barsch Learning-style Inventory (BLSI) categorized the students into auditory, tactile, and visual learners. To assess the students' reading comprehension ability, they sat for the reading comprehension test. Frequency distribution, independent t-test, and Pearson correlation test were used to analyze the data. The students' metacognitive awareness scores indicated that the females had a higher metacognitive awareness (x = 129.72) than the males (x = 129.62). Furthermore, statistically students from the day schools had a better metacognitive awareness level (x = 132.16) than those in the boarding schools (x = 125.86). Analysis showed that the males were more auditory (x = 18.36) and visual (x = 20.66) than the females. However, the females were more tactile (x = 17.70). Moreover, the day school students were more auditory (x = 18.38) and tactile (x = 17.51) than the boarding school students. Nevertheless, the boarding school students were more visual (x = 20.78).